Detailed Emotional Profile of Secondary Education Students Toward Learning Physics and Chemistry - Dávila-Acedo, María Antonia; Airado-Rodríguez, Diego; Cañada-Cañada, Florentina; Sánchez-Martín, Jesús (Frontiers in Psychology, 2021)
The present research arises from the need to identify the emotions that K-7 to K-10 students experience towards the learning of Physics and Chemistry, since it is a fact the decrease in the number of students choosing itineraries related to Science. Different blocks of contents have been considered in each subject in order to identify emotions towards each one of them. The considered sample consisted on 149 K-8 students, 152 K-9 students and 130 K-10 students from several middle and high schools in Badajoz (Spain) during the 2014-2015 school year. Students experienced more positive emotions towards the content of Chemistry than towards those of Physics. It has been detected a decrease in the mean frequency of positive emotions such as joy, fun, and tranquility from K-8 to K-10, as well as an increase in negative emotions such as boredom, anxiety, disgust, fear, nervousness, worry and sadness. It has been also found that positive emotions towards Chemistry contents are mainly related to teacher's method and attitude, while negative emotions towards Physics contents are related to the exclusive use of the textbook, solving Physics problems, or giving oral presentations of the topics in class.